Epidemiology, Prevalence And Diagnosis Of Falciparum Malaria With The Molecular Surveillance For Antimalarial Drug Resistant Gene Markers In Akure, Nigeria - Bunmi, Awosolu Oluwaseun (2022)
Malaria is a devastating parasitic disease of major public health problem worldwide, particularly in sub-Saharan African countries where Nigeria accounts for the highest burden of malaria disease. Currently, information on the epidemiology, diagnosis and prevalence of antimalarial drug resistant gene markers upon which malaria management and control could be based is scarce, particularly in Akure, Nigeria. Therefore, a randomized cross-sectional and hospital-based study was conducted to investigate the epidemiology and diagnosis of falciparum malaria and the molecular surveillance for antimalarial drug resistant gene markers in Akure, Nigeria. A total of 601 blood samples were collected from volunteered participants and examined through standard parasitological techniques of microscopy examination, rapid diagnostic test (RDT), nested polymerase chain reaction (nested PCR), and restriction fragment length polymorphism (RFLP). The participants information such as demographic, socioeconomic and environmental variables were collected through a structured and pre-tested questionnaire.